2020
DOI: 10.3390/brainsci10040226
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Orexin System for Prescription Opioid Use Disorder

Abstract: Prescription opioids are potent analgesics that are used for clinical pain management. However, the nonmedical use of these medications has emerged as a major concern because of dramatic increases in abuse and overdose. Therefore, effective strategies to prevent prescription opioid use disorder are urgently needed. The orexin system has been implicated in the regulation of motivation, arousal, and stress, making this system a promising target for the treatment of substance use disorder. This review discusses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 133 publications
(210 reference statements)
0
14
0
Order By: Relevance
“…Several recent reviews have comprehensively summarized the literature on the role of the paraventricular nucleus of the thalamus (PVT) in reward-seeking (James and Dayas, 2013 ; Kirouac, 2015 ; Do-Monte and Kirouac, 2017 ; Millan et al, 2017 ; Zhou and Zhu, 2019 ; Matzeu and Martin-Fardon, 2020 ). Based on a growing body of evidence, a consensus is emerging that PVT is part of a network that mediates appetitive/approach and aversive/avoidance behaviors, particularly during motivational conflicts (Choi and McNally, 2017 ; Choi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reviews have comprehensively summarized the literature on the role of the paraventricular nucleus of the thalamus (PVT) in reward-seeking (James and Dayas, 2013 ; Kirouac, 2015 ; Do-Monte and Kirouac, 2017 ; Millan et al, 2017 ; Zhou and Zhu, 2019 ; Matzeu and Martin-Fardon, 2020 ). Based on a growing body of evidence, a consensus is emerging that PVT is part of a network that mediates appetitive/approach and aversive/avoidance behaviors, particularly during motivational conflicts (Choi and McNally, 2017 ; Choi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of orexin in promoting arousal and waking from sleep has been well documented, with evidence showing that orexin plays a critical role in the regulation of sleep-to-wake transitions [ 3 , 17 ]. Additionally, an orexin deficiency is observed in narcolepsy, a disorder characterized by excessive sleepiness, sleep paralysis, and in some cases, episodes of cataplexy [ 3 , 17 ].…”
Section: Overview Of Physiological Roles Of the Orexin Systemmentioning
confidence: 99%
“…Neuropeptides orexin A and orexin B were first described in the late 1990s and were initially shown to regulate feeding behaviour [ 1 , 2 ]. Since their discovery, it has been shown that orexins are involved in diverse functions that range from the modulation of autonomic functions (i.e., food intake, sleep regulation, and cardiovascular function), and promotion of physical activity, as well as reward-seeking behaviour and higher cognitive functions, including attention, cognition, and mood [ 3 , 4 ]. While the roles of orexin in the regulation of food intake, sleep/wake cycles, and addictive behaviours have been extensively studied and reviewed [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], the role of these peptides in the modulation of mood and affect has not been as thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, our lab provided the first evidence that the orexin system mediates drug seeking behavior, reporting that the expression of conditioned place preference for cocaine (and morphine) is associated with Fos recruitment in LH orexin neurons (Harris et al, 2005). In the ~15 years since, a role for the orexin system has been extended beyond cocaine and morphine to all drugs of abuse tested, including alcohol (Brodnik et al, 2018;Hopf, 2020;James et al, 2017b;Matzeu and Martin-Fardon, 2020;Moorman, 2018;Walker and Lawrence, 2017). Fos activation of orexin neurons has been reported following alcohol sensitization in mice (Macedo et al, 2013) and in response to discriminative stimuli predictive of ethanol and cocaine availability (Dayas et al, 2008;Martin-Fardon et al, 2018).…”
Section: Orexin As a Mediator Of Cocaine And Alcohol Behaviorsmentioning
confidence: 99%